Characterizing pharmacogenetic programs using the consolidated framework for implementation research: A structured scoping review - McDermott, John H.; Wright, Stuart; Sharma, Videha; Newman, William G.; Payne, Katherine; Wilson, Paul (Frontiers in Medicine, 2022)
Several healthcare organizations have developed pre-emptive pharmacogenetic testing programmes, where testing is undertaken prior to the prescription of a medicine. This review characterizes the barriers and facilitators which influenced the development of these programmes. A bidirectional citation searching strategy identified relevant publications before a standardized data extraction approach was applied. Publications were grouped by programme and data synthesis was undertaken using the Consolidated Framework for Implementation Research (CFIR). 104 publications were identified from 40 programmes and 4 multi-center initiatives. 26 (66%) of the programmes were based in the USA and 95% in high-income countries. The programmes were heterogeneous in their design and scale. The Characteristics of the Intervention, Inner Setting, and Process domains were referenced by 92.5%, 80% and 77.5% of programmes respectively. A positive institutional culture, leadership engagement, engaging stakeholders, and the use of clinical champions were frequently described as facilitators to implementation. Clinician self-efficacy, lack of stakeholder knowledge, and the cost of the intervention were commonly cited barriers. Despite variation between the programmes, there were several similarities in approach which could be categorized via the CFIR. These form a resource for organizations planning the development of pharmacogenetic programmes, highlighting key facilitators which can be leveraged to promote successful implementation.